Ketahanan dan Pembebasan: Menganalisis Perlawanan Perempuan dalam No Fourth River melalui Lensa Feminisme Liberal - Wajiran, Wajiran (BASIS (Bahasa dan Sastra Inggris), 2024)
This study is aimed at analyzing the gender issues presented in a literary work by Christine Clayfield. This study explores the manifestations and impacts of women's resistance in the novel No Fourth River through the lens of liberal feminism, primarily drawing on Naomi Wolf's concept of power feminism. The analysis is centered on the main character, Christine, and her relentless struggle against patriarchal oppression. Critical forms of resistance, including desire, courage, independence, firmness, and hard work, are identified and explored in detail. Christine's journey reveals how these attributes enable her to confront and overcome systemic injustices. The findings underscore the importance of resilience and agency in women's liberation, empowering us to understand that these are the keys to significant personal and social changes, such as increased self-confidence, elevated social status, financial independence, and the fulfillment of love. This study contributes to the broader discourse on gender equality in literary studies, offering valuable insights into the ongoing struggle for women's rights and empowerment. By contextualizing Christine's resistance within the framework of liberal feminism, the research motivates us to continue the fight for gender equality, empowering us with the knowledge of the keys to personal and social changes.